PENDEKATAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SECARA KOMPREHENSIF - Muslih, Moh.; Wan Mamat, Wan Hasmah (IAIN Pekalongan, 2009)
In the context of national education, Islamic Religious Education (PAI) in school has a strong position because it has a formal juridical basis. In addition, Islamic Religious Education (PAI) has a very strategic position to form a good quality of learners on the development aspects of intellectual, emotional, and moral. However, between expectation and reality on the implementation of Islamic Religious Education in schools is still a sharp gap. The implementation of Islamic Religious Education in schools still has several drawbacks. Therefore, various efforts and attempts to solve the problems mentioned above are needed.